2014
DOI: 10.2147/ijn.s58932
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and characterization of silver nanoparticles using panchakavya, an Indian traditional farming formulating agent

Abstract: Synthesis of silver nanoparticles (AgNPs) with biological properties is of vast significance in the development of scientifically valuable products. In the present study, we describe simple, unprecedented, nontoxic, eco-friendly, green synthesis of AgNPs using an Indian traditional farming formulating agent, panchakavya. Silver nitrate (1 mM) solution was mixed with panchakavya filtrate for the synthesis of AgNPs. The nanometallic dispersion was characterized by surface plasmon absorbance measuring 430 nm. Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(44 citation statements)
references
References 28 publications
4
40
0
Order By: Relevance
“…Analysis of AgNPs through Energy dispersive X-ray (EDX) spectrometers confirmed the presence of elemental silver signal at 3 keV along (Fig. 2b) with other weak signals corresponding to oxygen and carbon, which could have essentially derived from the plant extract and consistent with previous studies [31,32]. FTIR measurement was carried out to identify the possible biomolecules in S. nigrum leaf extract responsible for capping leading to efficient stabilization of the silver nanoparticles (Fig.…”
Section: Synthesis and Characterization Of Agnpssupporting
confidence: 82%
“…Analysis of AgNPs through Energy dispersive X-ray (EDX) spectrometers confirmed the presence of elemental silver signal at 3 keV along (Fig. 2b) with other weak signals corresponding to oxygen and carbon, which could have essentially derived from the plant extract and consistent with previous studies [31,32]. FTIR measurement was carried out to identify the possible biomolecules in S. nigrum leaf extract responsible for capping leading to efficient stabilization of the silver nanoparticles (Fig.…”
Section: Synthesis and Characterization Of Agnpssupporting
confidence: 82%
“…7,8 However, the adverse effects of AgNPs need to be carefully evaluated before they could be used in antimicrobial products. Hence, phytosynthesized AgNPs were studied for antibacterial activity against phytopathogenic bacteria, namely, R. solanacearum and X. axonopodis.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Several studies reported AgNPs synthesis using biological materials, such as microorganisms, plant extracts, milk, and panchakavya. [7][8][9][10] Phytosynthesis of AgNPs using plant materials has an edge over microbial mediated synthesis owing to their immediate and large-scale production. 11,12 Thus, considerable attention is given to exploit the…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique is very important for the analysis of metal nanoparticles and provides information about the optical properties of the synthesized nanosize silver particles 11,12 . All the silver nanobioconjugates synthesized from grape seed extract and its component resveratrol showed distinct peak at 420nm, indicated the characteristic of AgNPs (Fig.…”
Section: Spectral Analysis Of Silver Nanobioconjugatesmentioning
confidence: 99%